Superconducting cavity material for the European XFEL. (August 2015) - Singer, W; Singer, X; Brinkmann, A; Iversen, J; Matheisen, A; Navitski, A; Tamashevich, Y; Michelato, P; Monaco, L
Abstract Analysis of the strategy for superconducting cavity material procurement and quality management is done on the basis of the experience with the cavity production for the European x-ray free electron laser (EXFEL) facility. An adjustment of the material specification to EXFEL requirements, procurement of material, quality control (QC), documentation, and shipment to cavity producers have been worked out and carried out by DESY. A multistep process of qualification of the material suppliers included detailed material testing, single- and nine-cell cavity fabrication, and cryogenic radiofrequency tests. Production of about 25 000 semi-finished parts of high purity niobium and niobium-titanium alloy in a period of three years has been divided finally between companies Heraeus, Tokyo Denkai, Ningxia OTIC, and PLANSEE. Consideration of large-grain (LG) material as a possible option for the EXFEL has resulted in the production of one cryogenic module consisting of seven (out of eight) LG cavities. LG materials fulfilled the EXFEL requirements and showed even 25% to 30% higher unloaded quality factor. A possible shortage of the required quantity of LG material on the market led, however, to the choice of conventional fine-grain (FG) material. Eddy-current scanning (ECS) has been applied as an additional QC tool for the niobium sheets and contributed significantly to the material qualification and sorting. Two percent of the sheets have been rejected, which potentially could affect up to one-third of the cavities. The main imperfections and defects in the rejected sheets have been analyzed. Samples containing foreign material inclusions have been extracted from the sheets and electrochemically polished. Some inclusions remained even after 150 μm surface layer removal. Indications of foreign material inclusions have been found in the industrially fabricated and treated cavities and a deeper analysis of the defects has been performed.